Characterization of Haemolysin of Staphylococcus aureus Isolated from Food of Animal Origin - Dwi Ariyanti; Siti Isrina Oktavia Salasia; Syarifudin Tato (Indonesian Journal of Biotechnology, 2011)
Staphylococcus aureus is an important pathogen bacteria causing food poisoning and various infection in animals and humans. Haemolysin is one of the virulence factors of Staphylococcus aureus. The aims of the research were to characterize haemolysins of Staphylococcus aureus isolated from various food of animal origin, phenotypic- and genotypically. In the present study, eleven Staphylococcus aureus isolated from various food of animal origins from traditional markets and supermarkets in Yogyakarta, Sidoarjo, Jakarta, and Bandung were characterized for haemolysin, pheno- and genotypically. Characterization of haemolysin phenotypically based on haemolysis pattern of Staphylococcus aureus on sheep blood agar plate. Genes encoding hemolysin were amplified with specific primers by using polymerase chain reaction (PCR) technique. The results of the studies showed that Staphylococcus aureus on sheep blood agar plates revealed an alpha haemolysis pattern (18,18%), beta haemolysis (27,27%) and gamma haemolysis (54,55%). Based on amplification of the gene encoding haemolysin of Staphylococcus aureus with specific primers showed hla genes (81,81%), and hla combined with hlb genes (18,18%). The amplification of gene hla and hlb had a single amplicon with a size of approximately 534 bp and 833 bp, respectively. The haemolysin characteristics of Staphylococcus aureus from various food of animal origin could be used as important information to control staphylococcal food poisoning.Keywords : Staphylococcus aureus, haemolysin, PCR, food of animal origins